Bài phát biểu của các đại biểu Quốc hội về vụ Thân Trung Hiếu tại phiên họp ngày 21/12/1991 (1991)
Nội dung Bài phát biểu của các đại biểu Quốc hội về vụ Thân Trung Hiếu tại phiên họp ngày 21/12/1991.